Pengaruh waktu tahan pack carburizing dan penggunaan media quenching cane molasses terhadap sifat mekanik dan struktur mikro baja karbon rendah - Darmo, S.; Sulistyowati, E. D.; Wahyu, R. M. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2022)
Pack carburizing is one of the methods used to increase the carbon content in steel by using solid media. In this study, the addition of carbon elements was carried out using teak wood charcoal and cow bone powder, after that in quenching using cane molasses. Variations used for holding time are 2 hours, 4 hours, and 6 hours, variations in cane molasses content used 10%, 20%, 30%, and the percentage comparison between cow bone powder and teak wood charcoal is 50%:50%. The results of this study show that the pack carburizing resistance time factor is more influential on the mechanical properties and microstructure of low carbon steel. The highest hardness value is found at a holding time of 6 hours with quenching cane molasses 20% of 799.95 kg/cm2 and the lowest hardness value is found without treatment of 162.62 kg/cm2. For the highest impact toughness is found without treatment of 2.02 Joule/mm2 and the lowest impact toughness value is found at holding time of 6 hours with quenching cane molasses 20% of 1.127 Joule/mm2. For microstructures formed after treatment, martensite structures are formed due to rapid cooling.